Role of Nanoparticles in Acoustical and Dielectric Measurements using Binary Non-Polar Fluid - Rohini, B.; Revathi, V. (Asian Journal of Chemistry, 2023)
In this work, the experimental values of dielectric constant and acoustical parameters for binary mixture (benzene + diethylamine) and hybrid CuO nanofluid (CuO + diethylamine + benzene) were studied for various molar fraction from 0.01 to 0.06 M with different temperatures ranging from 298 to 318 K. Molecular interaction depends on the concentration, inclusion of CuO nanoparticles and temperature. FTIR analyses also revealed that despite the rise in temperature, no bond breakdown between the molecules is found. The results demonstrate that the weak interaction due to van der Waals forces exist between the unlike molecules due to dipole-induced dipole interactions.